Insights into the Cenozoic geology of North Beirut (harbour area): biostratigraphy, sedimentology and structural history. Issue 2 (10th February 2020) - Clark, Germaine Noujaim; BouDagher-Fadel, Marcelle
Abstract : The biostratigraphy and sedimentology of the outcrops and bedrock recently exposed in archaeological excavations around the harbour area of Beirut ( 5 km²) unlock the geological and structural history of that area, which in turn are key to understanding the hydrocarbon and hydrogeological potential of the region. A key location (Site 2) of a studied outcrop section and newly uncovered bedrock is on the northern foothill cliff of East Beirut (Achrafieh). The outcrop section of carbonates is of Eocene beds overlain by conformable Miocene beds. The excavation of the slope bordering the outcrop uncovered a bedrock section of an early Pliocene shoreline of carbonate/siliciclastic sands at its base and topped by a beach-rock structure. The early Pliocene age of the shoreline section is dated by an assemblage of planktonic foraminifera that includes Sphaeroidinellopsis subdehiscens, Sphaeroidinella dehiscens and Orbulina universa . The Eocene carbonates of Site 2 extend the coverage of the previously reported Eocene outcrops in the harbour area. They form a parasequence of thin-bedded, chalky white limestones that includes the youngest fossil fish deposits in Lebanon ( Bregmaceros filamentosus ). The deposits are dated as early Priabonian by their association with the planktonic foraminiferal assemblage of Porticulasphaera tropicalis, Globigerinatheka barri, Dentoglobigerina venezuelana, Globigerina praebulloides, Turborotalia centralis and Borelis sp. The Middle Miocene carbonates that conformably overlie the early Priabonian, parasequence include a planktonic foraminiferal assemblage of Globigerinoides trilobus, Orbulina universa and Borelis melo . Elsewhere, in the harbour area, the preserved Eocene limestones are also overlain by conformable Miocene carbonate parasequences of Langhian–Serravallian age. Younger argillaceous limestone beds of the Mio/Pliocene age occur in the eastern central part of the harbour area and enclose an assemblage of Truncorotalia crassaformis, Globorotalia inflata and Orbulina universa . The three markers of old and recently raised structural blocks in the harbour area are a Lutetian/Bartonian marine terrace in the south west corner, a lower Pliocene shoreline carbonate section in the north east side and a Holocene raised beach of marine conglomerates in the north east corner of the area. The locations of these paleo-shorelines, less than 2 km apart, indicate a progressive platform narrowing of North Beirut since the Paleogene. This study underpins the geological complexity of the region and contributes to understanding the underlying geology, which will be needed for future regional archaeological, hydrocarbon and hydrogeological exploration.